2019
DOI: 10.1016/s2214-109x(19)30253-0
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the prevalence of soil-transmitted helminth infections in Sri Lanka to enable a more focused control programme: a cross-sectional national school survey with spatial modelling

Abstract: Summary Background In Sri Lanka, deworming programmes for soil-transmitted helminth infections became an integral part of school health in the 1960s, whereas routine antenatal deworming with mebendazole started in the 1980s. A 2003 national soil-transmitted helminth survey done among schoolchildren found an overall prevalence of 6·9%. In our study, we aimed to reassess the national prevalence of soil-transmitted helminth infections to enable implementation of a more focused control pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…reducing MDAs in low prevalence areas but increasing interventions in clusters of high transmission that persist. Our findings are similar to those from a school based survey in Sri Lanka (14).…”
Section: Discussionsupporting
confidence: 89%
“…reducing MDAs in low prevalence areas but increasing interventions in clusters of high transmission that persist. Our findings are similar to those from a school based survey in Sri Lanka (14).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are similar to those from a school-based survey in Sri Lanka. [ 17 ] This finding has potential implications for the national program as it may indicate communal behavioral change towards self-investment in preventive health. This could be a spillover effect of the sustained impact of school deworming in these districts, signaling that school-based MDA and accompanying community messaging raises awareness of the positive health outcomes of deworming, triggering treatment-seeking behavior in community members who do not have access to school MDAs but do have local access to affordable, high quality deworming medicines (Bangladesh generic manufacturers and formulations of benzimidazoles: CWW web-survey, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This could enable more focused strategies to target areas at risk of continued transmission. [11] In addition, Fronterre et al (2020) showed that geospatial estimated prevalences are a more efficient survey design than classic survey sampling strategies based on random sampling when evaluating transmission interruption. [12] qPCR model exhibited the highest estimated prevalence of infection of at least one STH per neighbourhood, followed by Telemann from two stools.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Cross-sectional surveillance studies can be costly and arduous. But geostatistical modelling showed to be an efficient method to improve surveillance at a reduced cost [ 11 , 12 ]. However, geospatial prediction might be sensitive to the diagnostic technique employed [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation